Local adaptation to different phytogeographic regions: habitat‐related variations in seed germination in response to temperature and salinity for two medicinal Salvia species from Jordan. Issue 1 (14th January 2016) - Al‐Gharaibeh, Mohammad M.; Hamasha, Hassan R.; Lachmuth, Susanne; Hensen, Isabell
Abstract: S alvia spinosa L. and S alvia syriaca L. are perennial medicinal herbs that occur in the Mediterranean, Irano‐Turanian and Saharo‐Arabian phytogeographic regions of Jordan. With respect to the seed germination requirements, prevailing environmental conditions in each phytogeographic region may promote local adaptation and consequently affect the distribution range of the species. Using seeds of both species collected from populations across the three regions, we tested responses to variations in temperature and salinity under laboratory conditions. Both species showed significant differences in cumulative germination percentages and germination rates (modified Timson Index) with temperature, while origin only significantly affected S . spinosa seeds. Both species germinated best under the highest temperature regime (32/20°C). The low temperature regime (8/4°C) completely inhibited germination in S . syriaca, wheras it led to 80% to 95% germination in S . spinosa, with significant variation being recorded between the phytogeographic regions. For both species, salt solutions of 0, 25 and 50 mM NaCl yielded the highest germination percentages and rates, which sharply and significantly declined at higher concentrations (100 and 200 mM NaCl). Our results provide evidence of local adaptation of the study species to salinity and temperature in the respective maternal environments, particularly in the Irano‐Turanian and Saharo‐Arabian regions. Such differentiation should be accounted for in future conservation planning. Abstract : We investigate local adaptation in the germination of two Salvia species from Jordan. Seed germination was examined in response to temperature and salinity. Optimum germination of both species was obtained at a temperature regime of 32/20°C.